Ability of systemic acquired resistance-saponin and a bacterial metabolite to reduce the soybean cyst nematode (Heterodera glycines) and the incidence of the sudden death syndrome (Fusarium virguliforme): Ability of systemic acquired resistance-saponin and a bacterial metabolite to reduce the soybean cyst nematode (Heterodera glycines) and the incidence of the sudden death syndrome (Fusarium virguliforme) - Radhi, Weasam Adnan; Husain, Eman Rathi; Ali, Sadeq Mohammed (Journal of Kerbala for Agricultural Sciences, 2018)
Experiments were conducted to examine the ability of biological seed treatments to reduce the Soybean Cyst Nematode and the incidence of Sudden Death Syndrome. Biological seed treatments included systemic acquired resistance (SAR)-Saponin, Bacterial metabolite, Bacillus firmus, Burkholderia renojensis, B. subtilis, and untreated seeds as control treatments. These seed treatments were used in test that included seed with no treatment, H. glycines alone, Fusarium virguliforme alone, and H. glycines + F. virguliforme. Seed applied products were received from and treated by Albaugh, LLC. Seeds were planted in 500 cm3 of a steam sterilized sand: soil mix (1:1/ V: V) in 10 cm dia clay pots and placed in a 2.54 cm depression in each pot with 2500 eggs of H. glycines, and 1g of F. virguliforme. Tests included the standards Abamectin and Fluopyram. Treatments were arranged in a randomized complete block design with five replications. Parameter measured included effects on plant growth, nematode life stage development and the incidence of SDS. At 60 days, the biological seed treatments produced no negative plant growth effects. Treatments that included bacterial metabolite and SAR-Saponin significantly reduced SCN cyst, juveniles, and eggs compared to the control. SAR-Saponin, and bacterial metabolite were statistically similar to the standards abamectin and fluopyram. SDS foliar disease was more severe in the treatments that included H. glycines compared with F. virguliforme than F. virguliforme alone. SDS foliar disease index reduced in treatments with saponin product compared to control in the bacterial metabolite and SAR-Saponin treatments respectively. Saponin and bacterial metabolite have shown potential for Sudden Death Syndrome and soybean cyst nematode management.